2007
DOI: 10.1111/j.1365-2672.2007.03435.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Helicobacter pylori in sewage and water using a new quantitative PCR method with SYBR® green

Abstract: Aims:  To demonstrate the application of a new quantitative polymerase chain reaction (qPCR) technique for the determination of Helicobacter pylori concentrations in water, and to use this method to investigate the occurrence of the bacteria in sewage. The other aim was to study the survival capacity and detectability of the bacteria in artificially contaminated groundwater at different temperatures of 4 and 15°C. Methods and Results:  The detection of H. pylori in water was aided by PCR using specific primers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 32 publications
1
35
1
1
Order By: Relevance
“…The findings of this study did not also agree with the study by Papiez et al that water-borne transmission of H. pylori could be an important source of infection in developing countries [8]. A study in Guatemala reported that H. pylori was unlikely to be transmitted by water [17] but epidemiological studies in many countries such as China [18], Lima Peru [19], and Colombia [20] had shown that infection was related to H. pylori contaminated water sources. Dube et al also reported that H. pylori could live in tap water in its infectious bacillary form, and in river water for several months in the nonculturable but viable cocoid form.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The findings of this study did not also agree with the study by Papiez et al that water-borne transmission of H. pylori could be an important source of infection in developing countries [8]. A study in Guatemala reported that H. pylori was unlikely to be transmitted by water [17] but epidemiological studies in many countries such as China [18], Lima Peru [19], and Colombia [20] had shown that infection was related to H. pylori contaminated water sources. Dube et al also reported that H. pylori could live in tap water in its infectious bacillary form, and in river water for several months in the nonculturable but viable cocoid form.…”
Section: Discussioncontrasting
confidence: 54%
“…Ahmed et al in South India also reported that the prevalence of H. pylori infection among people who drank well water was 92% compared with 74.8% of those who drank tap water (p<0.001) [3]. Several Epidemiological studies in many countries such as rural China, Lima Peru and Colombia had also shown that infection was related to H. pylori contaminated water sources [18][19][20]. However, in agreement with our study, Klein et al reported in a study in Guatemala that H. pylori were unlikely to be transmitted by water [17].…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, H. pylori was quantified by real-time PCR as described by Nayak and Rose (39). H. pylori was grown in BHI medium supplemented with 5% (vol/vol) FBS under microaerobic conditions at 37°C for 3 days.…”
Section: Vol 77 2011 Novel Bifidobacterium Strain Active Against Hmentioning
confidence: 99%
“…Infection with H. pylori is estimated to be 40-70% worldwide [18]. While H. pylori infection sources remain uncertain, recent studies have reported H. pylori DNA detection in water samples [19][20][21][22]. This evidence suggests an extensive distribution of H. pylori in aquatic environments and may indicate water itself as a potential infection source.…”
Section: H Pylorimentioning
confidence: 94%